Antibacterianos estimulam o crescimento dos biofilmes e produção de células persistentes de Candida albicans isoladas de fungemia - Portela, Fernando Victor Monteiro (2024)
Candidemia is one of the main causes of invasive fungal infections (IFI) in hospital settings, with high morbidity and mortality. Candida albicans is the leading pathogen identified, particularly affecting immunocompromised patients. Its virulence is linked to biofilm formation and the production of persistent cells (PC). Broad-spectrum antibiotics are a major risk factor due to the induced dysbiosis, which favors Candida colonization and mucosal barrier disruption. This study evaluated the influence of commonly used hospital antibacterials on biofilm formation and PC production by C. albicans strains isolated from fungemia. Six clinical strains were tested against amoxicillin, cefepime, vancomycin, amikacin, gentamicin, and ciprofloxacin at their peak plasma concentrations. An E. coli lysate was also used to simulate dysbiosis. Antifungal susceptibility, metabolic activity, biomass, biofilm structure, antifungal tolerance, and PC formation were assessed. Amoxicillin, cefepime, and vancomycin significantly enhanced biofilm formation, antifungal tolerance, and PC production. These results suggest that prolonged antibiotic use may contribute to persistent IFIs caused by C. albicans, posing a challenge to treatment and increasing the risk of recurrence.